Detrital zircon provenance of Permian to Triassic Gondwana sequences, Zealandia and eastern Australia. Issue 3 (3rd July 2022) - Adams, Christopher J.; Mortimer, Nicholas; Campbell, Hamish J.; Griffin, William L.
ABSTRACT: Permian Parapara Group and Triassic Topfer Formation are small clastic sedimentary outliers that rest on Cambrian to Devonian basement terranes in the Western Province of South Island, New Zealand. New detrital zircon U-Pb age datasets from three Parapara sandstones, one Topfer sandstone and four age-equivalent eastern Australian sandstones reveal age and provenance information about former Gondwana intracontinental basins. Youngest significant zircon age populations of 264 ± 6 and 261 ± 2 Ma in two Parapara Group sandstones and 215 ± 2 Ma in the Topfer sandstone match fossil ages and indicate broadly syn-depositional igneous activity. The provenance of the igneous detritus was probably the nearby Median Batholith and/or its volcanic equivalents. Zircons in a third Parapara sandstone are predominantly Cambrian and Precambrian in age and represent a separate petrofacies with a local Western Province basement terrane provenance. Intra-basin provenance switching between Gondwana margin arc and older basement sources is thus documented in Gondwana basin sequences in Zealandia, as well as those in Australia and Antarctica.